Three Kagulu Stories: Annotations, analysis, and word lists - Petzell, Malin (Studia Orientalia Electronica, 2015)
This article presents three linguistically analysed and annotated stories in the Kagulu language, together with a word list. Kagulu is a Bantu language, classified as G12, spoken by approximately 240,000 people in the Morogoro region of Tanzania. The objective of the article is to make these stories public for several reasons. First, there is very little published material in the Kagulu language at all. Second, the few anthropological stories that are published do not come with annotations, glossing or even a word-for-word translation into Swahili or English, which do not make these texts very meaningful from a linguistic perspective. Thirdly, these stories tell us about Kagulu life and Kagulu traditions and can thus be a tool in helping us to understand the culture and identity associated with the language. Finally, it is important that every language is written down, described and published. Undescribed languages run the risk of disappearing, while documenting a language forestalls its loss.